Sustained and Transient Vestibular Systems: A Physiological Basis for Interpreting Vestibular Function - Curthoys, Ian S.; MacDougall, Hamish G.; Vidal, Pierre-Paul; de Waele, Catherine (Frontiers in Neurology, 2017)
Otolithic afferents with regular resting discharge respond to gravity or low frequency linear accelerations, and we term these the static or sustained otolithic system. However in the otolithic sense organs there is anatomical differentiation across the maculae and corresponding physiological differentiation. A specialized band of receptors called the striola consists of mainly type I receptors whose hair bundles are weakly tethered to the overlying otolithic membrane. The afferent neurons which form calyx synapses on type I striolar receptors have irregular resting discharge and have low thresholds to high frequency (e.g. 500Hz) bone conducted vibration and air conducted sound. High frequency sound and vibration likely causes fluid displacement which deflects the weakly tethered hair bundles of the very fast type I receptors. Irregular vestibular afferents show phase locking, similar to cochlear afferents, up to stimulus frequencies of kilohertz. We term these irregular afferents the transient system signalling dynamic otolithic stimulation. 500Hz vibration preferentially activates the otolith irregular afferents, since regular afferents are not activated at intensities used in clinical testing whereas irregular afferents have low thresholds. We show how this sustained and transient distinction applies at the vestibular nuclei. The two systems have differential response to vibration and sound, to ototoxic antibiotics, to galvanic stimulation and to natural linear acceleration, and such differential sensitivity allows probing of the two systems. 500Hz vibration which selectively activates irregular otolithic afferents results in stimulus-locked eye movements in animals and humans. The preparatory myogenic potentials for these eye movements are measured in the new clinical test of otolith function – ocular vestibular evoked myogenic potentials. We suggest 500Hz vibration may identify the contribution of the transient system to vestibular controlled responses such as vestibulo-ocular, vestibulo-spinal and vestibulo-sympathetic responses. The prospect of particular treatments targeting one or the other of the transient or sustained systems is now being realized in the clinic by the use of intratympanic gentamicin which preferentially attacks type I receptors. We suggest that it is valuable to view vestibular responses by this sustained-transient distinction.